Effects of acceleration on skill level in skiers - Ma, C.; Sun, J. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: In a "U" shaped field, the skier must take off using snow slides in a determined territory, using the distribution of his body mass over his feet to control the direction, completing a variety of complex movements inherent to aerial sports. Objective: Study the effect of acceleration on skiers` skill levels. Methods: Peak moment angle and range of motion were measured in 12 U-shaped cross-country snow ski athletes with an average training period of over 5 years. The isokinetic muscle strength test parameters were analyzed with the characteristics and abilities inherent to the sport. The corresponding range of motion and the angle of acceleration were determined. The results were confronted with a literature search and discussed afterward. Results: The peak torque and relative peak torque of the flexor and extensor muscle groups on both sides of the athletes` hip and knee joints reduced with increasing angular velocity; the maximum peak torque of the extensors was significantly greater than that of the flexors at the same velocity (P?0.05). The current scientific literature predicted this inversely proportional relationship, but the angles obtained had not been explored. Conclusion: Athletes should pay attention to improving cognitive ability and active adjustment ability to complete their technical movements, promoting the development of controlled acceleration required by snow sports.